DAMPAK KEBIJAKAN PENDIDIKAN ISLAM (Study Tentang Lahirnya Kelas Elit Muslim di Indonesia) - Latifatul Khasanah (stit-islamic-village, 2019)
Education which applied in Indonesia influenced by many factors, for example: government political policy. Government policies ranging from colonial, pre independence day, post independence day until the new orde seemed to ignore Islamic education. This problem causing Islamic education institution have many weakness that have to find a solution. Islamic education institution lack of human resource, management, and fund. Muslims have not been able to optimally actualize Islam transformatively. Islamic education is less attractive to the public. This weakness can be solved due to the struggle of muslims and Islamic figure and the increase of government attention to Islamic education. Thus making various policies and regulations that bring Islamic education and Islamic education institutions increasingly play a role in the implementation of education in general in Indonesia. This can be seen from the number of recitation in hotels, the development of religious music, Muslim Television, Muslim newspaper and many young designer appeared to make a fashion trend in many national and international events.